Codicological and linguistic structure of Kitabu Bulghatil al-Mushtaq f i Lughat at-Turk wa-l-Qifchaq - Jafarov, Botir; Ganiyeva, Barchinoy (Turkic Studies Journal, 2025)
This article explores the linguistic, codicological and structural features of the 14th-century manuscript Kitabu Bulghatil al-Mushtaq fi Lughat at-Turk wa-l-Qifchaq written by Jamaliddin at-Turki. Composed during the Mamluk period in Egypt, this bilingual glossary was intended to assist Arabic-speaking scholars learn the Kipchak branch of the Turkic language family. Despite its significance in the field of historical Turkology, the manuscript remains underexplored. This study provides a philological and comparative analysis of the manuscript’s noun and verb sections, of the manuscript, identifying lexical correspondences and grammatical continuities between Kipchak Turkic and modern Turkic languages. The manuscript comprises two main sections: noun and verbs, each of which is further subdivided into chapters and subsections. The noun section contains rich thematic vocabulary, ranging from celestial terminology to everyday objects, with examples supported by Arabic and Turkic word pairs. The verb section is organized according to the Arabic alphabet and provides conjugations and derived forms that demonstrate remarkable morphological parallels with contemporary Turkic verb systems. This study highlights the manuscript’s pedagogical value and its complex structure, particularly the distinctive diamond-shaped arrangement of word pairs and the systematic strategies employed by the author to maintain semantic coherence and the sequential order of verb entries. Particular attention is given to placed on identifying missing or disordered folios and considering their implications for reconstructing and interpreting the manuscript’s original structure. Through rigorous linguistic comparison and philological analysis, the paperdemonstrates the continuity and resilience of lexical and grammatical features in the Turkic language tradition. This reaffirms the value of the manuscript as a critical intermediary in the historical interaction between Arabic and Turkic linguistic cultures. The research reveals that several folios were lost from the manuscript. It is believed that this loss occurred prior to foliation being added, as the lexical order between consecutive pages is disrupted and the catchword on page A does not correspond to the initial word on page B. Nevertheless, the folio numbers, added later, remain in the correct order, suggesting that the missing folios were absent when foliation was added. These findings make a valuable contribution to historical Turkic linguistics and manuscript studies, providing new insights into the codicological organization and pedagogical function of medieval Arabic – Kipchak glossaries. This comprehensive approach enriches our understanding of language contact and continuity within the Turkic world.